A Bibliometric Analysis on Public-Private Partnerships in Forest Management Using Bibliometrix R-Studio - Sajida; Ranjani; Fajri, Afrizal (Jurnal Manajemen Hutan Tropika, 2026)
The paper thereby joins the discussion on the fast-changing research landscape of public-private partnerships (PPPs) in forest management, providing a comprehensive bibliometric analysis. A dataset of 241 documents is retrieved from the Scopus database, whose analyses are done using advanced bibliometric tools available within the Bibliometrix package in R Studio. The study maps the intellectual structure of the field, identifies its key themes, and traces their evolution from 1987 to 2024. The bibliometric approach allows for the identification of core authors, influential journals, leading institutions, and geographical distribution of contributions, thereby painting a clear picture of the knowledge dynamics within the domain. The findings underline the central place PPP holds in the face of such global challenges as climate change, preservation of biodiversity, and sustainable development but bring into sharper focus the governance and institutional frameworks that underpin these partnerships. Special attention is paid to the policy discourses and academic debates surrounding PPP arrangements, especially in developing countries where forest governance is often contested. This paper identifies major emerging trends in future research, in particular, the integration of cutting-edge technologies like machine learning. It fills this critical gap with a holistic overview of the current state of the art in forest management PPPs, thus offering useful insights for researchers, policymakers, and practitioners who want to enhance the effectiveness of such partnerships in achieving sustainable environmental outcomes.